SIMPLE FLATS FOR RENT (RUSUNNAWA) FOR WHO? CASE STUDY: TELUK KELAYAN FLATS, BANJARMASIN CITY - Nurul Azkar; Rabiyatul Adawiyah (Jurnal Ekonomi, 2022)
The construction of simple rented flats (Rusunawa) is an integral part of the slum management program and at the same time providing decent housing for low-income people. This study aims to analyze the benefits of the Teluk Kelayan Flats in the City of Banjarmasin for low-income people, including victims of relocation of slum areas. In order to obtain data, observations and interviews were carried out with several informants from the Housing and Settlement Area Office of the City of Banjarmasin, managers and occupants of the flats and several residents who were victims of relocation. The results of the data analysis show that the development policy for the Teluk Kelayan Flats has not been used optimally because not all the rooms are filled. In fact, the existing occupants are not low-income residents who are victims of the relocation of slum areas.